2015
DOI: 10.1038/nsmb.3063
|View full text |Cite|
|
Sign up to set email alerts
|

The active site of O-GlcNAc transferase imposes constraints on substrate sequence

Abstract: O-GlcNAc transferase (OGT) glycosylates a diverse range of intracellular proteins with O-linked N-acetylglucosamine (O-GlcNAc), an essential and dynamic post-translational modification in metazoans. Although this enzyme modifies hundreds of proteins with O-GlcNAc, it is not understood how OGT achieves substrate specificity. In this study, we describe the application of a high-throughput OGT assay to a library of peptides. We mapped sites of O-GlcNAc modification by electron transfer dissociation MS and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
179
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(198 citation statements)
references
References 69 publications
18
179
1
Order By: Relevance
“…Glycosites from human T cells show only a weak homology sequence, in agreement with previous reports (50,51). The absence of a strict consensus motif as well as the possible transfer of UDP-GlcNAc to a Ser/Thr near the originally targeted Ser/Thr on a protein has stymied the study of O-GlcNAc function.…”
Section: Discussionsupporting
confidence: 71%
“…Glycosites from human T cells show only a weak homology sequence, in agreement with previous reports (50,51). The absence of a strict consensus motif as well as the possible transfer of UDP-GlcNAc to a Ser/Thr near the originally targeted Ser/Thr on a protein has stymied the study of O-GlcNAc function.…”
Section: Discussionsupporting
confidence: 71%
“…In sharp contrast, OGT has a much more restricted substrate sequence specificity (22); thus O-GlcNAcylation typically occurs at only one or a few Ser/Thr residues within these Ser/Thr-rich sequences. It has been suggested that there is little OGT substrate bias toward a specific amino acid at P+1 (22), in contrast to our finding that Pro at P+1 blocks O-GlcNAcylation. We investigated, therefore, whether Pro could act to guide OGT to specific Ser/Thr sites.…”
Section: Reciprocal Interplay Does Not Occur On Ser/thr Sites Targetecontrasting
confidence: 56%
“…3A). This motif is based on several sets of reported data, namely the O-GlcNAcylation motif extracted from the 26 best-known OGT substrates (22), the PX(S/T) O-GlcNAc motif described for HLA class I-bound peptides (23), the protein sequences O-GlcNAcylated in this study (SI Appendix, Table S2), and the finding reported in this paper that phosphorylation at P−3 hampers O-GlcNAcylation. Using bioinformatics analysis, we found that these sequences of four amino acids not only are very common in the human proteome (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). Consistent with our results, Cdh1 was recently identified in a screen using in vitro OGT assays on substrate peptides derived from annotated protein kinase substrates (37).…”
Section: Discussionsupporting
confidence: 80%